2019
DOI: 10.1016/j.ymgme.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing of RNA reveals novel targets of resveratrol with possible implications for Canavan disease

Abstract: Resveratrol (RSV) is a small compound first identified as an activator of sirtuin 1 (SIRT1), a key factor in mediating the effects of caloric restriction. Since then, RSV received great attention for its widespread beneficial effects on health and in connection to many diseases. RSV improves the metabolism and the mitochondrial function, and more recently it was shown to restore fatty acid βoxidation (FAO) capacities in patient fibroblasts harboring mutations with residual enzyme activity. Many of RSV's benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…We found that SLC52A1 and CYP1A1 were the most significantly up- and downregulated gene in RES-treated human endothelial cells, respectively. This was consistent with the RNA sequencing results observed in fibroblasts, which showed that SLC52A1 was significantly up-regulated after RES treatment [ 58 ]. Studies have shown that CYP1A1 may be involved in the pathogenesis of atherosclerosis and the occurrence of diabetes mellitus and its vascular complications [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that SLC52A1 and CYP1A1 were the most significantly up- and downregulated gene in RES-treated human endothelial cells, respectively. This was consistent with the RNA sequencing results observed in fibroblasts, which showed that SLC52A1 was significantly up-regulated after RES treatment [ 58 ]. Studies have shown that CYP1A1 may be involved in the pathogenesis of atherosclerosis and the occurrence of diabetes mellitus and its vascular complications [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…SIRT6 influences the expression of several glycolytic genes such as GLUT1, aldolase, pyruvate dehydrogenase kinase 1 (PDK1), and phosphofructokinase 1 (PFK1) [134]. Furthermore, RSV is known as an activator of SIRT1 and has been related to diabetes progress as a target for its treatment [135,136], inflammation, and neuroprotection [137]. There are data suggesting that RSV has hypoglycemic properties in diabetic rats and restore glycolytic enzyme activities [138,139].…”
Section: Inhibition Of Glucose Uptake By Resveratrolmentioning
confidence: 99%
“…Although safety profiles of TZD were documented in young patients with type 1 diabetes [110], further studies are required to understand the effects on behavior and long-term safety of TZD in children with ASD. Novel approaches using natural FAO activators like RSV are particularly appealing, due to their proven application for correction of CPT2- and VLCAD-deficiency in patient cells [103,117].…”
Section: Molecular Regulation Of Mitochondrial Fao: the Ppar Pathwaymentioning
confidence: 99%